Two new Auletta Schmidt, 1870 (Axinellidae; Demospongiae; Porifera) from Brazil - Cavalcanti, Thaynã; Recinos, Radharanne; Pinheiro, Ulisses (Zootaxa, 2017)
The genus Auletta Schmidt, 1970 comprises 14 valid species, with six known from the Atlantic Ocean. The genus was previously recorded for the Brazilian coast only in 1967 from surveys in Pernambuco State. The present paper describes two new Auletta from Northeastern Brazil. Auletta akaroa sp. nov. is from Alagoas State and it has a stalked tubular shape and small sinuous styles and strongyles. Auletta laboreli sp. nov. was found in Pernambuco State and it is a sponge with a cylindrical and cavernous body composed of styles with blunt and telescopic tips and sinuous strongyles. Both new species were compared with the other valid species of Auletta. The spicule complement and external morphology of the new species are discussed.